Iatrogenic visual aura: a case report and a brief review of the literature - Buture A; Khalil M; Ahmed F (Dove Medical Press, 2017)
Alina Buture, Modar Khalil, Fayyaz Ahmed Neurology Department, Hull Royal Infirmary, Hull, UK Abstract: Iatrogenic migraine aura following transseptal catheterization has only rarely been reported in the literature. We report the case of a 60-year-old female who presented with new onset of migraine with visual aura 1 day after transseptal cryoballoon catheter ablation for atrial fibrillation. The patient had a 5-year history of typical migraine without aura and had never experienced visual aura before the cardiac intervention. The neurological examination, fundoscopy, and blood tests were normal. The magnetic resonance imaging of the brain showed small vessel ischemia without evidence of vessel ischemic changes in the occipital lobes and large blood vessel disease. A change in the characteristics of existing migraine could occur following an iatrogenic episode, which in this case was catheter ablation for atrial fibrillation. A new onset of aura is considered an indication for a brain scan as it may signify underlying new pathology. Keywords: migraine aura, iatrogenic, transseptal catheterization